2008
DOI: 10.1182/blood-2008-05-155846
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and pathologic significances in increase in serum interleukin-6 (IL-6) and soluble IL-6 receptor after administration of an anti–IL-6 receptor antibody, tocilizumab, in patients with rheumatoid arthritis and Castleman disease

Abstract: Interleukin-6 (IL-6) plays pathologic roles in immune-inflammatory diseases such as rheumatoid arthritis (RA) and Castleman disease. By inhibiting IL-6 receptors (IL-6Rs), tocilizumab (a humanized anti-IL-6R antibody) ameliorates the symptoms of these diseases and normalizes acute-phase proteins, including Creactive protein (CRP). We found that tocilizumab treatment increased serum levels of IL-6 and soluble IL-6R (sIL-6R). To investigate the pathologic significance of these increases, we analyzed the kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

66
523
9
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 689 publications
(627 citation statements)
references
References 19 publications
66
523
9
11
Order By: Relevance
“…Conversely, the percentage of patients who maintained sufficient trough concentrations of TCZ was decreased after switching, suggesting that the serum trough concentration of TCZ could not be maintained in certain patients with high body weights. It is conceivable that disease activity was increased because IL‐6 signal transduction could not be completely inhibited 14. In contrast, the trough concentration of TCZ and efficacy slightly increased after switching in patients with low body weights (<50 kg).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the percentage of patients who maintained sufficient trough concentrations of TCZ was decreased after switching, suggesting that the serum trough concentration of TCZ could not be maintained in certain patients with high body weights. It is conceivable that disease activity was increased because IL‐6 signal transduction could not be completely inhibited 14. In contrast, the trough concentration of TCZ and efficacy slightly increased after switching in patients with low body weights (<50 kg).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CRP level is normalized when the serum TCZ concentration is ≥1 μg/ml, because TCZ can be bound to ≥95% of soluble IL‐6 receptors 14. Serum TCZ concentrations can be indirectly monitored through CRP concentrations, although the serum TCZ concentration is substantially maintained with individual differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that IL-6 stimulates the production of vascular endothelial growth factor in the synovium of RA patients, thus contributing to pannus formation (16). Recent studies of IL-6R inhibition using tocilizumab have shown good clinical responses in RA (3,17) and other immune-mediated diseases (3).…”
mentioning
confidence: 99%
“…While this may be a tractable surrogate measurement for cell surface RO, the physiological relevance of soluble RO must be assessed. Another option is to quantify the accumulation of a ligand for the receptor in the circulation as an indirect measure of RO 29, 30, 31, 32. However, the natural ligand for the receptor may be unknown or, if known, may bind to multiple receptors, in which case, the ligand levels may not be increased following administration of drugs.…”
Section: Considerations When Developing Flow Cytometry‐based Ro Assaysmentioning
confidence: 99%